The phospholipase D pathway modulates the inflammatory response of retinal pigment epithelium cells exposed to high glucose concentrations - Mateos, Melina Valeria (2018)
Purpose: Diabetic retinopathy (DR) is one of the main causes of visual dysfunction and blindness in working-age adults in which chronic hyperglycemia, oxidative stress and inflammation are key pathogenic players. The aim of this work was to study the role of the phospholipase D (PLD) pathway in retinal pigment epithelium (RPE) cells exposed to an in vitro DR model. Methods: Human RPE cell lines (ARPE-19 and D407) were exposed to high glucose (HG) concentrations (16.5 or 33 mM) or to normal glucose concentration (NG, 5.5 mM) for 4, 24 or 72 h. Osmotic controls were performed with mannitol (Man). After experimental treatment western blot (WB), immunocytochemistry and qPCR assays were performed. Cell viability was evaluated using the MTT reduction assay and PLD activity was measured as [3H]-phosphatidylethanol ([3H]-PEth) generation from [3H]-phosphatidylcholine in the presence of 0.4% ethanol. Results: Exposure to HG increased reactive oxygen species levels and caspase-3 cleavage and reduced cell viability after 72 h of incubation. In addition, short term HG exposure (4 h) induced the activation of early events, that involve PLD and ERK1/2 signaling, nuclear factor kappa B (NF-κB) nuclear translocation and IκB phosphorylation. An increment in pro-inflammatory interleukins (IL-6 and IL-8) and cyclooxygenase-2 (COX-2) mRNA levels was observed after 24 h of HG exposure. The effect of selective pharmacological PLD1 (VU0359595) and PLD2 (VU0285655-1) inhibitors demonstrated that ERK1/2 and NF-κB activation were downstream events of both PLD isoforms. The increment in IL-6 and COX-2 mRNA levels induced by HG was reduced to control levels in cells pre-incubated with both PLD inhibitors. Furthermore, the inhibition of PLD1, PLD2, the MEK/ERK pathway (with U0126) and COX-2 (with celecoxib) prevented the loss of cell viability induced by HG. Conclusions : Our results demonstrate that HG exposure induces PLD activation in RPE cells, leading to ERK1/2 activation, IκB degradation, NF-κB nuclear translocation and expression of pro-inflammatory ILs and COX-2 and reduced cell viability. Our findings are the first evidence that classical PLDs participate in the inflammatory response of RPE cells exposed to HG and leads us to postulate these signaling enzymes as potential therapeutic targets for DR treatment